Genres of music in Slovenia in the Middle Ages - Snoj, Jurij (De musica disserenda, 2015)
Five distinct genres of music existed in Slovenian ethnic territory during medieval times: vernacular music in oral tradition, Latin plainchant, Glagolitic chant, medieval polyphony, and German Minnesang. After presenting the sources and their contents, and summarizing what is presently known, the article discusses the prospects for future research on medieval plainchant within Slovenian ethnic territory.